SUPERIORITY OF RHYTHMIC STABILIZATION AND MULLIGAN TAPING TO ISOMETRIC EXERCISE AND MULLIGAN TAPING COMBINATION FOR REDUCING SHOULDER DISABILITY IN SURFERS - Putra, Yudi Pramana; Widnyana, M.; Utama, A.A Eka Septian; Kamayoga, I Dewa Gede Alit (Sport and Fitness Journal, 2024)
Abstract— Shoulder disability is a condition where there is limitation in the shoulder region which causes the inability of the shoulder to carry out functional movements and is often found in the extreme and repetitive sports activities which involve the shoulder as the main movement maker during the sport. Shoulder disability often becomes serious injury for surfers when to do paddle movements, shoulder disability injury are often worse by less optimal interventions, so it need more efforts to solve shoulder problems more quickly and efficiently. In this study, the researchers will comparing the effectiveness of intervention PNF "rhythmic stabilization" with isometric exercise intervention where the two interventions focus on increasing shoulder stabilization and the both of that intervention will combined with the Mulligan's technique taping to adding externally support on shoulder. The aim of this study was to prove the effectiveness of adding a new method in reducing one of the symptoms and sources of shoulder disability, especially shoulder instability with the intervention combination of proprioceptic neuromuscular facilitation “rhythmic stabilization” and mulligan's taping which is better than the combination of isometric exercise intervention and mulligan's taping in reducing shoulder disability in surfers at Double Six Beach Seminyak Badung Bali. The research method using experimental research with pre-test and post-test two group design. There are two groups with the number of each group consisting of 16 samples chosen randomly with the block permutation technique. Group 1 will receive a combination of proprioceptic neuromuscular facilitation “rhythmic stabilization” and mulligan's taping, while group 2 will receive isometric exercise and mulligan's taping. Disability was measured using the SPADI (Shoulder Pain and Disability Index) questionnaire. The research was conducted at a physiotherapy clinic in Denpasar. The results of the study after the Paired T-Test was carried out in each group with a p value <0.05, this indicated that there was a significant difference between the results of the pre-test and post-test in each group. The different test between groups was carried out by the Independent T-Test, obtaining a p value <0.05, this indicated that there was a significant difference between the two intervention treatment groups. The conclusion of this study is the addition of a new method in reducing one of the symptoms and sources of shoulder disability, namely shoulder instability with the intervention of a combination of proprioceptic neuromuscular facilitation “rhythmic stabilization” and mulligan's taping which has proven to be significantly better than the combination of isometric exercise and mulligan's taping in reducing the shoulder. disability on surfers at Double Six Beach Seminyak Badung Bali.   Keyword: Proprioceptic Neuromuscular Facilitation , Rhythmic Stabilization, Isometric Exercise, Mulligan’s Taping , Shoulder Disability, Shoulder Pain And Disability Index